ERADICATING INCOME INEQUALITY IN LOWER MIDDLE-INCOME COUNTRIES - Pratysto, Tangguh; Panjaitan, Ingrid (Muhammadiyah University Press, 2019)
Studying the distribution of income is an important issue to know what factors which affect to make income distribution more equitable, what factors can be the key to resolving the problem of income inequality, and shortening the distance between the poor and the rich. This paper studies the relationship between human capital, inflation rate, unemployment rate, physical capital, fiscal expenditure, gross domestic product growth, and urbanization on income inequality in 52 Lower Middle-Income Countries throughout 1990-2014. The authors estimate the impact of seven independent variables on income inequality as a dependent using Prais-Winsten with the robust model over period 1990-2014 at 52 Lower Middle-Income Countries. The results indicate an increase in human capital (gross school enrollment tertiary) can make the income distribution more even in the long run. The writers conclude that increases in human capital can reduce Gini coefficient and hence make income distribution fairer.